CSR Transformation Towards Sustainability: a Case Study of Environmental Program in PT Kideco Jaya Agung (Kampung Iklim Program in Klempang Sari Village, Paser Regency) - Arga, Khariryan; Chao, Liu; Utha, Maria Ariesta (Syntax Literate, 2025)
This research explores the change of CSR at PT Kideco Jaya Agung (KJA), specifically the research is focused on Climate Village program (ProKlim program) at Klempang Sari Village, Indonesia. In a descriptive qualitative approach, the study explores planning, implementation and stakeholder involvement through data collection and analysis of fieldwork and data on file. Results indicate that the CSR inversion integrates environmental governance, community empowerment, and contributes to the alignment with Sustainable Development Goals (SDG 13 and 15). Tangible results are mangrove restoration, water saving, circular waste activities. This research utilizes Goal Attainment Theory, Stakeholder Theory, Program Logic Model and Triple Bottom Line to assess impact. The strong internal validity was further enhanced by demonstrating "how the CSR in the extractive sector can move beyond philanthropic behavior and compliance towards strategic and participatory sustainability. The paper provides lessons for including ESG in rural climate action through multi-level collaboration and local institutionalization.